The side-to-side differences of bone mass at proximal femur in female rhythmic sports gymnasts - Wu, J.; Ishizaki, S.; Kato, Y.; Kuroda, Y.; Fukashiro, S. (Journal of Bone and Mineral Research, 1998)
This cross-sectional study examined the side-to-side differences of the bone mineral density (BMD) at proximal femora in female rhythmic sports gymnasts (RSGs). The hypothesis on which the study is based is that gymnasts use a different leg in take-off (left leg) and in landing (right leg) and therefore differ in the loading for the left and right legs. The gymnasts made up two groups: the regular group, which consisted of 15 regular players who had trained for about 28 h/week, and the substitutes group, which consisted of 8 substitute players who had trained for about 12 h/week. The control group consisted of 10 nonathletic college women who had not participated in any kind of regular sports activity. BMD (g/cm2) was measured in three hip sites using the XR-26 dual-energy X-ray absorptiometer scanner. Muscle strength at knee extensors (EXT) and flexors (FLX) was examined using an isokinetic dynamometer (CYBEX6000), and the vertical ground reaction force was determined with a force platform during take-off and landing movements. In the regular players, the BMDs of the left leg were significantly higher than those of the right leg at the femoral necks, greater trochanters, and Ward's triangles (p < 0.01 to approximately 0.005). The side-to-side differences were 4.7 to approximately 9.6%. Regarding the strength parameters, the left side was greater than the right side significantly at EXT 60 degrees/s (p < 0.01), although the overall side-to-side difference was small. In the substitutes, the BMDs at the three sites mentioned above were also higher in the left leg than the right, but the side-to-side difference was statistically significant only at Ward's triangles (93%, p < 0.05). The side-to-side difference of strength was not significant. In the controls, there were small left-to-right differences of the BMDs, ranging from -1.8 to 0.5%, which was significantly lower than in the regular players at each site. The overall average strength measurements were larger in the right leg than in the left except at the 120 degrees/s. The side-to-side difference was statistically significant at EXT 30 degrees/s and 60 degrees/s (p < 0.05). The peak force was greater in take-off than in landing, and the unit time force during take-off was significantly greater than that during landing (p < 0.001). In conclusion, regarding the side-to-side difference of the BMD at proximal femora, our results demonstrate: that the left leg for take-off had higher measurements than the right leg for landing in both gymnasts' groups, which accounts for the vertical ground reaction force during take-off being greater than that during landing; that the difference in the regular players group was greater than that in the substitute group, which can be explained because the regular players practiced much more than the substitutes did; and that there was no difference in the control group.